2012
DOI: 10.1007/s10965-011-9770-8
|View full text |Cite
|
Sign up to set email alerts
|

Proton conducting gel electrolytes based on polymethylmethacrylate doped with sulfuric acid solutions in N,N-dimethylformamide

Abstract: In the work presented time-stable proton conducting gel electrolytes based on polymethylmethacrylate doped with sulfuric acid solutions in N,N-dimethylformamide were synthesized. The dependences of gels conductivity on the acid concentration and the molecular mass of PMMA at 25-65°C are studied. The thermal stability of electrolytes was estimated. The FT-IR (ATR) spectroscopy was used for understanding of mechanism of proton transfer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…It has been reported that proton conduction in dilute H 2 SO 4 solution (<5 wt%) follows Arrhenius behaviour. 30 We believe that the hopping of protons between dissociated HSO 4 − anions via hydrogen bonding accounted for the observed conductivities. 31…”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…It has been reported that proton conduction in dilute H 2 SO 4 solution (<5 wt%) follows Arrhenius behaviour. 30 We believe that the hopping of protons between dissociated HSO 4 − anions via hydrogen bonding accounted for the observed conductivities. 31…”
Section: Resultsmentioning
confidence: 81%
“…The temperature-dependent conductivities of the hydrogels holding the micellar solution also approximately satisfied the Arrhenius law, as observed for the EDBSA micellar solution. 15 3 30 We believe that the hopping of protons between dissociated HSO 4 À anions via hydrogen bonding accounted for the observed conductivities. 31…”
Section: Proton Conductivities Of the Templated Pam Hydrogels Holding...mentioning
confidence: 79%
“…Dependences of the specific conductivity of the binary solutions [ y (acid)–DMF] and gel electrolytes with compositions of 9 wt % PMMA–[ y (acid)–DMF], prepared on the basis of these binary solutions, on the corresponding acid concentration at 298 K: (a) H 3 PO 4 , (b) H 2 PO 3 F, and (c) H 2 SO 4 . The data on the conductivity of 9 wt % PMMA–[ y H 2 SO 4 –DMF] gels were taken from our previous work …”
Section: Resultsmentioning
confidence: 99%
“…This process was the object of our spectroscopic investigation. We studied the possibility of hydrogen‐bond formation between the components of the PGEs (acid–DMF and acid–PMMA) earlier for PMMA‐based electrolytes doped with sulfuric acid solutions in DMF [9 wt %PMMA–( y H 2 SO 4 –DMF)], where the region of the stretching modes of CO groups [ν(CO)] of DMF (1660 cm −1 ) and PMMA (1727 cm −1 ) were considered. The analysis of the same frequency range for PMMA‐based electrolytes doped with phosphoric acid solutions in DMF [9 wt % PMMA–( y H 3 PO 4 –DMF)] was performed within this study.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, lithium salts containing GPEs mainly depend upon electron rich functional groups of polymers for their movement, and hence they lack higher power density. Ambient temperature conductivities obtained for some of these proton conducting polymeric electrolytes were higher than 10 −3 s cm −1 [8][9][10][11][12]. The particular choice of dilute HCl as dopant is because of its well dissociative property.…”
Section: Introductionmentioning
confidence: 98%